2018
DOI: 10.1177/0271678x18803623
|View full text |Cite
|
Sign up to set email alerts
|

Acute pain alters P-glycoprotein-containing protein complexes in rat cerebral microvessels: Implications for P-glycoprotein trafficking

Abstract: P-glycoprotein (PgP) is the major drug efflux pump in human cerebral microvessels. PgP prevents pathogens, toxins and therapeutic drugs from entering the CNS. Understanding the molecular regulation of PgP activity will suggest novel mechanisms to improve CNS drug delivery. Previously, we found that during peripheral inflammatory pain (PIP) (3 h after λ carrageenan injection in the rat paw), PgP traffics to the cortical microvessel endothelial cell plasma membrane concomitant with increased PgP activity. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…This is consistent with previous immunogold immunocytochemistry studies that demonstrated P-gp localization at the nuclear envelope in microvascular endothelial cells in human and rat brain [122]. The trafficking mechanism that has been identified and characterized by our group involves phosphorylation of caveolin-1, which is the primary signal that causes enhanced recruitment of P-gp to the plasma membrane in response to acute inflammatory pain [121]. This highly significant finding is supported by our previous work, which demonstrates that P-gp colocalizes with caveolar proteins (i.e., caveolin-1, cavin-1, and cavin-2) in membrane fractions derived from intact brain microvessels [123].…”
Section: Pain Modulates Abc Transporter Expression and Traffickingsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with previous immunogold immunocytochemistry studies that demonstrated P-gp localization at the nuclear envelope in microvascular endothelial cells in human and rat brain [122]. The trafficking mechanism that has been identified and characterized by our group involves phosphorylation of caveolin-1, which is the primary signal that causes enhanced recruitment of P-gp to the plasma membrane in response to acute inflammatory pain [121]. This highly significant finding is supported by our previous work, which demonstrates that P-gp colocalizes with caveolar proteins (i.e., caveolin-1, cavin-1, and cavin-2) in membrane fractions derived from intact brain microvessels [123].…”
Section: Pain Modulates Abc Transporter Expression and Traffickingsupporting
confidence: 91%
“…The complexity of P-gp-mediated transport regulation at the BBB in pain is emphasized by knowledge that pain triggers increased P-gp trafficking from the endothelial cell nucleus to the plasma membrane [21,120,121]. Using our detergent-free subcellular fractionation method [109], we demonstrated that P-gp traffics from the nucleus and increases P-gp protein expression and activity at the plasma membrane in response to the CIP stimulus (Figure 3) [120].…”
Section: Pain Modulates Abc Transporter Expression and Traffickingmentioning
confidence: 99%
“…(C) Cross-section of a microvessel labeled with lectin (red), an antibody to the tight junction (TJ) protein claudin-5 (green), and DAPI (blue). Modified with permission from Tome et al (2018).…”
Section: Molecular Composition and Regulation Of Tjs At The Bbbmentioning
confidence: 99%
“…Rat cortical microvessels were isolated as previously described [42,43]. Briefly, rats were anesthetized with intraperitoneal injection of 80:10 mg/kg ketamine:xylazine, decapitated and the brains placed in ice-cold buffer A (136.9 mM NaCl; 2.7 mM KCl; 1 mM CaCl 2 ; 1.5 mM KH 2 PO 4 , 8.1 mM Na 2 HPO 4 ; 0.5 mM MgCl 2 ; 5 mM glucose; 1 mM sodium pyruvate, pH7.4) supplemented with Roche EDTA-free Complete Protease Inhibitor cocktail, Sigma protease inhibitor cocktail and 2 mM phenylmethylsulfonyl fluoride.…”
Section: Isolation Of Cortical Microvesselsmentioning
confidence: 99%